Nanocarriers for methotrexate delivery/codelivery in the frame of cancer diagnostics and treatment: a review - Mukhtar, Mahwash; Ezra Manicum, Amanda-Lee; Shojaei Barjouei, Masoumeh; Eshaghi Malekshah, Rahime; Behzadmehr, Razieh; Rahdar, Abbas; Ghotekar, Suresh; Baino, Francesco (Frontiers in Biomaterials Science, 2023)
Cancer is one of the most life-threatening family of diseases that cause death worldwide. As a highly researched and successful therapeutic agent, methotrexate (MTX) treats many solid tumours, hematologic malignancies, and autoimmune illnesses. Despite many benefits, MTX induces drug resistance and limits plasma half-life due to its poor pharmacokinetics. The variable biological availability have prompted researchers to investigate innovative delivery strategies for enhancing its therapeutic qualities. To develop more suitable MTX formulations, nanoparticles (NPs) have recently gained a significant interest. A wide range of NPs, including polymer-based NPs, carbon-based NPs, lipid-based NPs, as well as inorganic NPs, can be deliver cancer chemotherapeutics such as MTX. Loading MTX into NPs can provide a delivery system that has shown great promise to carcinoma therapy. In this review, we will describe the feasibility of NP-based strategies to deliver MTX in cancer therapy, outlining the current state of the art and the challenges/promises for the future.